Modelling human queuing at Kuantan cinema - Abdul Qadir Jailani, Muchtar (2016)
This thesis presents a comparison between types of queue system simulation by using Discrete Event Simulation (DES). In our literature review we identified a gap in comparing the applicability of this type of queue system. Hence, we focused our research on reactive and different level of detail of proactive of human behavior in service system.The aim of our thesis is first to identify the possible queuing type’s model, second is to develop different queuing types using discrete event simulation and lastly to compare the developed queuing type models based on waiting times and no. of customer served. To reach that we investigate both similarities and differences between model results performance and the similarities and differences in model difficulty performance.The comparison of the simulation is reach by using scenario method. We conduct three scenarios in same environment and DES method, the different is we use the different type of queue system in the simulation. In the first scenario(cinema ticket service) we use single queue line and multi service or counter, second scenario we still use single queue line and multi service but we reduce two counter services, and lastly third scenario we use multi queue line and multi service.The result from the experiment reveals that both single line and multi-line suitable for that kind of environment. In addition, multi-line and multi-service is more suitable in this environment for achieving the shorter waiting time to serve the customer in counter ticket cinema.